Enterococcus faecium Mediastinitis Complicated by Disseminated Candida parapsilosis Infection after Congenital Heart Surgery in a 4-Week-Old Baby - Hanna Renk; Felix Neunhoeffer; Florian Hölzl; Michael Hofbeck; Matthias Kumpf (Case Reports in Infectious Diseases)
Background. Cardiac surgery offers multiple treatment options for children with congenital heart defects. However, infectious complications still remain a major cause of morbidity and mortality in these patients. Mediastinitis is a detrimental complication in children undergoing cardiac surgery. The risk of mediastinitis after delayed sternal closure is up to 10%. Case Presentation. We report a case of Enterococcus faecium mediastinitis in a 4-week-old female baby on extracorporeal membrane oxygenation after Norwood procedure. Although repeated antibiotic irrigation, debridement, and aggressive antibiotic treatment were started early, the pulmonary situation deteriorated. Candida parapsilosis was isolated from bronchoalveolar lavage after pulmonary hemorrhage. Disseminated C. parapsilosis infection with pulmonary involvement was treated with liposomal amphotericin B. Subsequently, inflammatory markers increased again and eventually C. parapsilosis was isolated from the central venous catheter. Conclusion. Children undergoing delayed sternal closure have a higher risk of mediastinitis. Therefore, antibiotic prophylaxis, for example, for soft tissue infection seems justified. However, long-term antibiotic treatment is a risk factor for fungal superinfection. Antifungal treatment of disseminated C. parapsilosis infection may fail in PICU patients with nonbiological material in place due to capacity of this species to form biofilms on medical devices. Immediate removal of central venous catheters and other nonbiological material is life-saving in these patients.